Partitioning between recoding and termination at a stop codon–selenocysteine insertion sequence - Kotini, Suresh Babu (Nucleic Acids Res, 2015)
Selenocysteine (Sec) is inserted into proteins by recoding a UGA stop codon followed by a selenocysteine insertion sequence (SECIS). UGA recoding by the Sec machinery is believed to be very inefficient owing to RF2-mediated termination at UGA. Here we show that recoding efficiency in vivo is 30–40% independently of the cell growth rate. Efficient recoding requires sufficient selenium concentrations in the medium. RF2 is an unexpectedly poor competitor of Sec. We recapitulate the major characteristics of SECIS-dependent UGA recoding in vitro using a fragment of fdhF-mRNA encoding a natural bacterial selenoprotein. Only 40% of actively translating ribosomes that reach the UGA codon insert Sec, even in the absence of RF2, suggesting that the capacity to insert Sec into proteins is inherently limited. RF2 does not compete with the Sec incorporation machinery; rather, it terminates translation on those ribosomes that failed to incorporate Sec. The data suggest a model in which early recruitment of Sec-tRNA(Sec)–SelB–GTP to the SECIS blocks the access of RF2 to the stop codon, thereby prioritizing recoding over termination at Sec-dedicated stop codons.